LAW AND ETHICAL PARADIGMS IN THE DISCOURSE ON WESTERN PHILOSOPHY AND ISLAMIC PHILOSOPHY - Citra Widyasari S; Mukarramah Mukarramah; Iskandar Iskandar; Rahma Pramudya Nawangsari (Sekolah Tinggi Agama Islam Sadra, 2024)
There are differences in the approach to law and ethics in Western philosophy compared to law and ethics in Islamic philosophy. Western philosophy itself is divided into several schools, including natural law philosophy, legal realism or positivistic philosophy, historical philosophy of law, sociological philosophy of law, and utilitarianism. These schools have different views on the position of law and ethics. In the discourse of Islamic philosophy, Law and Ethics or Morality are seen as interrelated principles. While Western philosophy is divided into several schools and dichotomizes between Law and Ethics, in Islamic philosophy they are integrated into the view that law and ethics are a unity and represent the spirit of Islamic teachings. This research aims to explain the role of law and ethics in Western philosophical schools. This research will explain how Western philosophical thought relates to law and ethics, and how the integration of law and ethics occurs in the context of Islamic philosophy. This research is a type of literature review or bibliographic study. The method applied in this research is descriptive analysis using a comparative approach. In the issue of Law and ethics, Western philosophical schools are divided into two views: those that unite law and those that separate law and ethics. The view that unites law and ethics includes natural law philosophy and historical philosophy of law. The view that separates law and ethics includes legal realism, positivism, social jurisprudence, and utilitarianism. Meanwhile, in the context of Islamic philosophy, the relationship between law and ethics is considered an integrated dimension in human life that cannot be separated.